How does joint evolution of social trust and land administration shape economic outcomes? Evidence from Viet Nam - Dang Duc Anh; Kim Khoi Dang; Thi Lan Vu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper examines how the interaction of social trust and institutions, such as land administration, affects household economic decisions in Viet Nam. Using a panel dataset of rural households from 2008 to 2014, we show that negative consequences of the duration of land administration on credit access, agricultural investment, and land use rights have been mitigated in communes with higher level of trust. These results support the view that trust complements formal institutions.
Keywords: Z13; O13; K4; O53; 330; Trust; land administration; agricultural investment; Viet Nam